Hubungan Perilaku Pencegahan 3M Plus Dengan Kejadian Demam Berdarah Dengue (DBD) Di Wilayah Kerja Puskesmas Bintuhan Kabupaten Kaur - Sanisahhuri; Khairani, Nurul; Fatchia Rindang Asih; Santoso Ujang Effendi (Gayaku Publisher, 2024)
Data from the World Health Organization (WHO) says that in 2022, every year it is estimated that 50-100 million cases of dengue hemorrhagic fever (DHF) will occur in the world. The highest number of DHF in Kaur Regency is in the Bintuhan Community Health Center working area, namely 21 cases in 2022. This research aimed to determine the relationship between 3M Plus prevention behavior and DHF incidents in the Bintuhan Community Health center working area, Kaur Regency. This type of research was Analytical Survey, with a Case Control research design. The case population was all heads of families who had family members suffering from DHF in the period January 2022-April 2023 in the Bintuhan Community Health Center working area, Kaur Regency, totaling 33 families. The control population was all families whose family members did not suffer from DHF in the Bintuhan Community Health Center working area in the period January 2022-April 2023, totaling 3,525 families. The number of samples in this study was 66 heads of families consisting of 33 case samples and 33 control samples, with a ratio of 1:1. The data analysis used in this research was univariate analysis, bivariate analysis using the Chi-Square test. The research results showed that of the 66 heads of families, 39 heads of families (59.1%) implemented 3M Plus prevention behavior and 33 heads of families (50.0%) experienced DHF. There was a relationship between 3M plus prevention behavior and the incidence of DHF in the strong relationship category and odd ratio (OR) = 48,438. It is recommended that the Bintuhan Community Health Center, Kaur Regency, develop strategies for preventing and controlling DHF, one of which is holding aducation about DHF.